Strategi Pemasaran Global pada PT Indofood Sukses Makmur Tbk : A Literarure Review - Daffa Quthbir Robani; Dhafa Herlambang Wisanggeni; Yoga Aditiya Pratama; Mohamad Zein Saleh (Universitas 45 Surabaya, 2025)
PT Indofood Sukses Makmur Tbk has become one of the Indonesian companies that has succeeded in the global market thanks to a mature marketing strategy. This article discusses global marketing phenomena, challenges, and opportunities faced by large companies, as well as the strategies that Indofood implements in expanding its market internationally. The main focus includes product analysis, innovation, and cultural adaptation carried out by Indofood. The literature review approach was used to dig deeper into the company's global marketing strategy. Through this discussion, the article provides insight into how a company can compete in the global market.